Importance of Computed Tomography in Determining Displacement in Scaphoid Fractures - Gilley, Emily; Puri, Sameer K.; Hearns, Krystle A.; Weiland, Andrew J.; Carlson, Michelle G. (Journal of Wrist Surgery, 2018)
Background Displaced scaphoid fractures have a relatively high rate of nonunion. Detection of displacement is vital in limiting the risk of nonunion when treating scaphoid fractures.Questions/Purpose We evaluated the ability to diagnose displacement on radiographs and computed tomography (CT), hypothesizing that displacement is underestimated in assessing scaphoid fracture by radiograph compared with CT.Materials and Methods Thirty-five preoperative radiographs and CT scans of acute scaphoid fractures were evaluated by two blinded observers. Displacement and angular deformity were measured, and the fracture was judged as displaced or nondisplaced. Scapholunate, radiolunate, and intrascaphoid angles were measured. Radiograph and CT measurements between nondisplaced and displaced fractures were compared. Intraobserver reliability was measured.Results  Reader 1 identified 12 fractures as nondisplaced on radiograph, but displaced on CT (34%). Reader 2 identified 9 fractures as nondisplaced on radiograph, but displaced on CT (26%). For displaced fractures, the mean intrascaphoid angle was over three times greater when measured on CT than on radiograph (56 vs. 16 degrees). Scapholunate angle >65 degrees and radiolunate angle >16 degrees were significantly associated with displacement on CT. Interobserver reliability for diagnosing displacement was perfect on CT but less reliable on radiograph.Conclusion Scaphoid fracture displacement on CT was identified in 26 to 34% of fractures that were nondisplaced on radiograph, confirming that radiographic evaluation alone underestimates displacement. These results underscore the importance of CT scan in determining displacement and angular deformity when evaluating scaphoid fractures, as it may alter the decision on treatment and surgical approach to the fracture. We recommend considering CT scan to evaluate all scaphoid fractures.Level of Evidence Level III.
Keywords: scaphoid; fracture; displacement; computed tomography